Digital marketing strategy through mobile application to increase room sales At Ibis Styles Bali Legian Hotel - I Gusti Ayu Suci Nurtirtawaty; Ni Gst Nym Suci Murni; Ni Ketut Bagiastuti; Made Ruki (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This study aims to identify the market segment of Ibis Styles Bali Legian Hotel and to find out the digital marketing strategy through the mobile application in increasing room sales. This study used descriptive qualitative research methods and used primary data through interviews, observations, documentation and questionnaires. The results showed that the market segments at Ibis Styles Bali Legian were mostly FIT (Free Independence Travelers) from the Distribution and inbound segments, and the majority of tourists from Australia. The digital marketing strategy through the mobile application in increasing room sales were through promotion of products and services for brand awareness, strengthening online reputation and traffic growth, through social media, online banners on the landing page, optimization of SEO, SEM and keywords to facilitate searches/browses, collaborate with influencers and travel bloggers as well as provide extra benefits in transactions made through mobile applications. With this strategy, impacting the reservations via mobile applications is dominating the market segment by 85% of the total market and increase the sales from year to year.